The Association Between Stress Level and Smoking Behavior in Gondanglegi Junior High School Boys - Masluha; Faizatur Rohmi; Wiwit Dwi Nurbadriyah (Journal of Nursing Science Update (JNSU), 2022)
Stress is a common issue in youth nowadays. Stress that arises is often caused by biological, psychological, family, school, and friend factors. In times of stress, the body automatically carries out stress management, one of which is smoking. This study aimed to determine the relationship between stress levels with smoking behavior in junior high school boys in Gondanglegi. This research uses a descriptive-analytic method with a cross-sectional approach. The population is junior high school boys in Gondanglegi, and the sample is 36 respondents. Sampling was done by purposive sampling technique. The measuring instruments used were the DASS questionnaire and the smoking behavior questionnaire. Processing data using Spearman Rank statistical tests. The results showed that 29 respondents (80.6%) were in the normal stress category, and 19 respondents (52.8%) in the smoking behavior category were light smokers. Based on the statistical test results obtained, Spearman Rank p value = 0.039 <α (0.05), then H0 is rejected, meaning that there is a relationship between stress levels with smoking behavior in adolescent boys in Gondanglegi. These results indicate a significant relationship between stress levels and smoking behavior among teenage boys in Gondanglegi. So it is hoped that there will be counseling for teenagers for stress management and smoking behavior at school